Morphological and Molecular Characterization of Pufferfish from Lekok Coastal Area, Pasuruan Indonesia - Panjaitan, Viona Angelina Erlan; Rangga, Adam Dwi; Sulung, Cahya Ajeng Valenta Tresna; Rahayu, Dwi Anggorowati; Khaleyla, Firas; Nugroho, Endik Deni; Rusdianto, Rusdianto; Mamat, Noorhidayah Binti (Biosaintifika: Journal of Biology & Biology Education, 2025)
Pufferfish belong to the Tetraodontidae family, which consists of 28 genera and 184 species; however, there are limited studies on the species from East Java, especially Pasuruan. This indicates the need for the collection of more accurate morphological and genetic resources as an important step for its conservation. Therefore, this study was conducted to identify pufferfish species found in the Lekok Coastal Waters, Pasuruan District, through morphological characterization and molecular analysis using DNA barcoding of the COI gene. A total of 12 samples were collected from the Lekok Coastal Waters, Pasuruan Regency. Fin samples were stored in 96% absolute ethanol. DNA extraction, polymerase chain reaction (PCR), and sequence analysis were performed using bioinformatics tools, the BOLD system, and the Automatic Barcode Gap Discovery (ABGD) web platform. Phenetic taxonomy was further applied using Ntysc to enhance the robustness of genetic analysis. The results showed that there were identified five pufferfish species were identified: Lagocephalus spadiceus, Chelonodontops patoca, Cyclichthys orbicularis, Arothron stellatus, and Arothron reticularis. High haplotype diversity (Hd) of 1 and nucleotide diversity (π) of 0.1 indicate significant genetic variation. The frequency of parsimonious informative sites was 22.6%, with 13 polymorphic sites and an overall ts/tv ratio of 2.2. The phylogenetic tree showed unambiguous branching patterns among species. These findings are supported by morphological and molecular identification results, which indicate the presence of five species of pufferfish along the Lekok Coast, Pasuruan Regency.